Creation or disruption? Doubts from the internet applications in China's rural sector - Feng Zhou; Hongtu Deng (Journal of Innovation & Knowledge (JIK), 2023)
To address the current large gap in research on the Internet applications in the Chinese rural sector, this paper explores the effect of these applications on the labor productivity of Chinese farmers from a creative destruction perspective. First, we construct a model to analyze the direct and indirect paths of the Internet applications impact on the productivity of farm households at the theoretical level; second, we conduct an empirical study corresponding to the theory based on micro-survey data obtained from China's first nationwide large-scale social survey project. Specifically, we verified the Internet applications direct effect on farm household labor productivity through the mean treatment effect approach and explored the efficiency and mechanism of action of the Internet productivity effect in the rural sector using the mediating effect model, Probit model, and the counterfactual analysis framework. The study finds that the productivity effect of the rural Internet applications still has a certain gap compared with the urban sector, although it is not at the 'Solow's paradox' stage. Further discussion reveals that the Internet adoption in rural areas is a process of 'creative destruction', and its destructive effects are dominant at this stage, while the creative effects still need to be further explored. This paper emphasizes that, for developing countries, accurately identifying the development stage of the Internet applications and further exploring its creative role is an important way to improve labor productivity in rural areas, and it is also an important step to promote the construction of digital villages.
Keywords: J20; O18; 650; Internet applications; Farm labor productivity; Creative destruction; Intermediary effect